ChemInform Abstract: Alcoholysis of Malonyl Peroxides to Give Peracids. Issue 24 (27th May 2016) - Lapitskaya, Margarita A.; Vil', Vera A.; Daeva, Elena D.; Terent'ev, Alexander O.; Pivnitsky, Kasimir K.
Abstract: The alcoholysis of malonyl peroxides of type (I) is studied.